ART THERAPY TO REDUCE DEPRESSION DUE TO DOMESTIC VIOLENCE AT “X” COMMUNITY IN AMBON - Violenta Soukotta; Monty P. Satiadarma (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2018)
This research is aimed to the practice of Art Therapy to reduce Depression due to Domestic Violence of “X” Community in Ambon. Individuals undergoing domestic violence are at high risk of having many negative psychological impacts. One of its impact is depression. Individuals with depression due to domestic violence need to get a social support and psychotherapy. Art Therapy is one of a form of psychotherapy that can be suggested to treat depressed individuals. This study used qualitative research method and was conducted from April 22nd 2017 to May 22nd 2017. The participants in this study were three women who had been undergoing domestic violence for some years. The result of this study showed that art therapy had reduced the level of depression of the three participants. Art therapy hass affected participants in these areas: (a) gaining self-knowledge, (b) medium of catharsis and relaxation, (c) expression of emotions and feelings, (d) facilitating self development, (e) stimulating self awareness, (f) enhancing self confidence through the success of creating the art works, (g) reducing stress and boredom. The therapeutic relations bonded between the participants and researcher might also have affected participants through their feelings of being helped and receiving deep concern from others.Penelitian ini bertujuan untuk mempraktekkan Terapi Seni demi mengurangi Depresi akibat Kekerasan Dalam Rumah Tangga pada Komunitas